2006
DOI: 10.1530/eje.1.02156
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-sensitizing agents in polycystic ovary syndrome

Abstract: Insulin-sensitizing agents have been recently proposed as the therapy of choice for polycystic ovary syndrome (PCOS), since insulin resistance and associated hyperinsulinemia are recognized as important pathogenetic factors of the syndrome. Moreover, since almost all obese PCOS women and more than half of those of normal weight are insulin resistant, and therefore present some degree of hyperinsulinemia, the use of insulin sensitizers should be suggested in most patients with PCOS. Insulin sensitizer treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(29 citation statements)
references
References 112 publications
2
27
0
Order By: Relevance
“…Insulin sensitizing agents such as metformin, ioglitazone and troglitazone, have been proposed as treatment for PCOS-associated hyperinsulinemia [129,130]. Metformin may antagonize some hyperandrogenic signs, by reducing total and free testosterone concentrations [131,132].…”
Section: Treatment Of Pcosmentioning
confidence: 99%
“…Insulin sensitizing agents such as metformin, ioglitazone and troglitazone, have been proposed as treatment for PCOS-associated hyperinsulinemia [129,130]. Metformin may antagonize some hyperandrogenic signs, by reducing total and free testosterone concentrations [131,132].…”
Section: Treatment Of Pcosmentioning
confidence: 99%
“…A change in endometrial gene and protein expression after in vitro stimulation with metformin was demonstrated, including a diminished decidualisation process and changes in genes relevant to implantation (Germeyer et al 2011). Metformin concomitantly restored menstrual cycles and increased conception rates in women with PCOS (Pasquali and Gambineri 2006). Notably, PCOS patients with a positive response to metformin treatment had significantly lower pretreatment sex-hormone binding globulin (SHBG) levels (Wassell et al 2011).…”
Section: Metforminmentioning
confidence: 99%
“…The demonstrated efficacy of insulin-sensitizing drugs, such as metformin, troglitazone and pioglitazone, in improving ovulatory function and reducing androgen excess in PCOS provided additional proof to support insulin resistance's pathogenic role in PCOS. However, side effects such as nausea and diarrhea (in the case of metformin) and increased body weight (in the case of pioglitazone) may reduce patients' compliance and limit the use of these drugs [4][5][6].…”
Section: Introductionmentioning
confidence: 99%